Psychometric Properties of the Fear of Monkeypox Scale among Men Who Have Sex with Men - Chung-Ying Lin; Amir H. Pakpour; Mark D. Griffiths; Chien-Wen Lin; Cheng-Fang Yen (Taiwanese Journal of Psychiatry)
Objectives: An outbreak of monkeypox (Mpox) appeared suddenly and rapidly spread worldwide during 2022. Men who have sex with men (MSM) are at a high risk of contracting Mpox compared to other cohorts. In the present study, we intended to examine the psychometric properties of a newly developed scale among MSM: the Fear of Mpox Scale (FMS) assessing the fear of Mpox. Methods: This is an online study. The factor structures of the FMS were first examined using exploratory factor analysis. After determining the factor structure, the FMS was further examined for (a) internal consistency using Cronbach’s α and (b) concurrent validity using correlations with anxiety, depression, and risk perception of contracting Mpox, and the known-group validity by comparing the scores of the FMS across MSM with sexual orientation and education level. Results: In total, 389 MSM participated in this study. The results indicated that the FMS had a one-factor structure. The FMS had acceptable internal consistency (α = 0.911) and concurrent validity (associated with anxiety [p < 0.01], depression [p < 0.001], and risk perception [p < 0.001]). No significant difference in the FMS scores was found between the groups with regard to sexual orientation or educational level. Conclusion: The results of the present study indicated that the psychometric properties of the FMS were good and that they can be used for assessing the fear of Mpox among MSM.